El derecho fundamental a la vida del clon humano - Rodríguez Avalos, Yovar Osven (2011)
uman cloning is the biotechnological technique that reduces man to a status thing or instrument, as a justification of that claim is often fundamentally paternalistic desire satisfaction infertile couples and the benefit to the health of people with serious illness; the first is often called reproductive cloning and therapeutic cloning second. So, to be performed at the cloning of embryonic cells, it is necessary to determine at what point life comes to protect him, taking from this that life begins with fertilization, starting with the man from the moment their continuous development. In turn, to originate the human clone genetic material of the human species, the first is a human being and thus person. Therefore, to clone human practices violate the right to life of embryos that are subjected to such practices, with the so-called therapeutic cloning, the most seriously injured this right, because in it, once the embryo is removed after it has been obtained stem cells, unlike the also so-called reproductive cloning, since it at least allows the development of the embryo, even if not in all cases, as there is selectivity in determining which embryos after produced and deserve to continue in their development. Thus, whatever the type of artificial cloning question, it violates the fundamental right to life of the human clone, because it as a human being is a person and, as such deserves the full respect of their rights, especially of that without which others can not enjoy, as is the fundamental right to life.